A novel sliding mode guidance law without line-of-sight angular rate information accounting for autopilot lag. Issue 16 (10th December 2017) - He, Shaoming; Wang, Jiang; Wang, Wei
ABSTRACT: This paper proposes a new composite guidance law to intercept manoeuvring targets without line-of-sight (LOS) angular rate information in the presence of autopilot lag. The presented formulation is obtained via a combination of homogeneous theory and sliding mode control approach. Different from some existing observers, the proposed homogeneous observer can estimate the lumped uncertainty and the LOS angular rate in an integrated manner. To reject the mismatched lumped uncertainty in the integrated guidance and autopilot system, a sliding surface, which consists of the system states and the estimated states, is proposed and a robust guidance law is then synthesised. Stability analysis shows that the LOS angular rate can be stabilised in a small region around zero asymptotically and the upper bound can be lowered by appropriate parameter choice. Numerical simulations with some comparisons are carried out to demonstrate the superiority of the proposed method.